2019
DOI: 10.1002/anie.201901687
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Signatures of Chirality Recognition Between α‐Pinene and Alcohols for Theory Benchmarking

Abstract: Chirality recognition between largely rigid molecules can be applied as ab enchmark for the description of intermolecular forces by theoretical methods,b ecause one constituent is merely mirrored, so other deficits of the methods such as neglect of anharmonicity should mostly cancel. To test this approach, mixed OH···p-bridged dimers between the enantiomers of the bicyclic monoterpene a-pinene and the chiral secondary alcohols borneol, a-fenchol, isopinocampheol, and 1-phenylethanol were formed in as upersonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…In previous FTIR jet studies 59,73,90 a single band at 3653 cm À1 was observed in the monomer region, which was assigned to the most stable conformer gÀ 73 (part of the training set). This band is confirmed as the most intense with Raman detection, with additional signals now revealed at 3670 and 3646 cm À1 (Fig.…”
Section: Propargyl Alcoholmentioning
confidence: 79%
“…In previous FTIR jet studies 59,73,90 a single band at 3653 cm À1 was observed in the monomer region, which was assigned to the most stable conformer gÀ 73 (part of the training set). This band is confirmed as the most intense with Raman detection, with additional signals now revealed at 3670 and 3646 cm À1 (Fig.…”
Section: Propargyl Alcoholmentioning
confidence: 79%
“…P is thus a rare case of a permanently chiral alcohol with one dominant conformer, while most occur in multiple energetically close conformations due to the low symmetry of the HOC α C β torsional potential. 28,62 In conclusion, B is expected to occur as a 1:1-mixture of two rapidly interconverting transiently chiral conformers, whereas the ratio of the analogous permanently chiral conformers of P can be controlled by the enantiomeric excess of the sample.…”
Section: Monomer Conformationsmentioning
confidence: 94%
“…Initial searches for minima and transitions states were conducted with the B3LYP [34][35][36][37] functional together with Grimme's D3 correction with two-body terms and Becke-Johnson damping 38 and the def2-TZVP basis set 39 . This choice is based on previous performance for systems with chirality recognition 6,28 . Results were reoptimized with the larger minimally augmented may-cc-pVTZ basis set 40 and complemented by B2PLYP-D3 41 (also with two-body terms and BJ-damping), ωB97X-D 42 and M06-2X 43 functional results, also using may-cc-pVTZ.…”
Section: Computational Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it was found that in hydrogen‐bonded complexes, LD interactions can largely influence the preferred structures . As such, systematic studies of molecular complexes, where both hydrogen bonding and LD interactions can form, are powerful tools to study the relative contributions of hydrogen bonding and LD to molecular interactions …”
Section: Introductionmentioning
confidence: 99%